Pengaruh Pemilihan Saw Blade Pada Proses Pemotongan Dalam Fabrikasi Besi Girder 2-G-(F)-750 - Haryudwitomo, Galih; Burhan, Nanang; Santoso, Deri Teguh (Universitas Nusantara PGRI Kediri, 2024)
In the fabrication process of a series of piperacks, accurate workpiece results are needed in a fast time, therefore procedures are needed that can support the speed and accuracy of fabrication to fulfill PT Pertamina's wishes so that the RDMP RU V Balikpapan project takes place quickly. One part of the piperack fabricated by PT Arkha Jayanti Persada is iron girders. Because the process of checking the quality of parts of the piperack series is carried out by PT Pertamina very strictly, the results of the fabricated iron girders are also required to obtain precision iron girders at the right time but not injuring the tools and machines owned by PT Arkha Jayanti Persada. The purpose of this study is to analyze the results of 4 different blades. From the research results, it was found that cutting the 2-G-(F)-750 girder took 119 minutes using a saw blade 41 x 1.3 x 5300 – 10 TPI. With the same blade speed, replacing the saw blade with a 14 TPI tooth profile speeds up the cutting time to 85 minutes (29 %).